Real-world impact of the introduction of chemo-immunotherapy in extended small cell lung cancer: a multicentric analysis - Bonanno, Laura; Calvetti, Lorenzo; Dal Maso, Alessandro; Pavan, Alberto; Bao, Loc Carlo; De Nuzzo, Mattia; Frega, Stefano; Sartori, Giulia; Ferro, Alessandra; Pasello, Giulia; Morandi, Paolo; Aprile, Giuseppe; et al. (Frontiers in Immunology, 2024)
Recent clinical trials demonstrated longer survival in extended small cell lung cancer (SCLC) patients treated with immunotherapy in addition to chemotherapy. However, the magnitude of benefit is modest and the impact in real-world setting has to be fully established.We collected clinical data and radiological imaging of patients affected by extended or relapsing SCLC and consecutively treated according to clinical practice between 2016 and 2023. As primary end-point, we compared pre-defined outcome indicators before and after the introduction of chemoimmunotherapy (May 2020): 6-month and 12-month progression free survival (PFS) rate, 12-month and 18-month overall survival (OS). Among those who were treated after May 2020, patients who did not receive immunotherapy according to treating physician' choice were included in the analysis to minimize clinical selection bias.The analysis included 214 patients: 132 (61.7%) were treated in an Academic cancer center and 82 (38.3%) in two community hospitals; 104 were treated before May 2020. Median PFS of the overall study population was 4.8 months (95% confidence interval [95% CI]: 4.4-5.4), median OS was 7.1 months (95% CI: 6.3-7.7).Estimated PFS and OS were significantly longer in patients treated after May 2020 with hazard ratio (HR) for PFS and OS of 0.61 (95% CI: 0.46-0.81, p < 0.001) and 0.70 (95% CI: 0.52-0.93, p = 0.015), respectively. 6-month PFS rate increased from 27% to 40% (p = 0.04) while 12-months PFS raised from 1% to 11% (p = 0.003). 12-month and 18-month OS rate increased from 15% to 28% (p = 0.03) and 2.1% to 12% (p = 0.009), respectively. After May 2020 the median number of hospitalization days per patient decreased significantly and the incidence of severe AEs was similar. Among patients treated with chemo-immunotherapy, the onset of immune-related AEs was associated with improved PFS and OS (HR 0.55, 95% CI: 0.35-0.89, p = 0.012 and HR 0.47, 95%CI 0.28-0.77, p = 0.002, respectively).The real-world analysis shows a meaningful improvement of outcome indicators after the introduction of chemo-immunotherapy, with reduction of the duration of hospitalization, thus supporting the use of chemo-immunotherapy and the need for further biomarker research.